Intensity of climacteric symptoms in postmenopausal women - Santos, Thaiene Rodrigues dos (2016)
Objective: to evaluate the characteristics and intensity of climacteric symptoms in postmenopausal women. Methods: a cross-sectional, descriptive study with systematic probabilistic sampling, consisting of 247 women in post menopause, who answered the Questionnaire of Women’s Health. To evaluate the intensity of climacteric symptoms the Menopausal Index of Blatt and Kupperman was used. Statistical analysis was performed using the Statistical Package for Social Sciences software version 17, a significance level of 5% and 95% confidence intervals for all analyzes were adopted. Results: 36.8% of women had mild climacteric symptoms, 56.3% moderate and 6.9% severe. In descending order hot flushes, irritability and sleep disorders reached the highest intensity ratios. Conclusion: the Menopausal index of Blatt and Kupperman (25.34) showed symptoms of moderate intensity. Hot flushes showed to be the symptom of highest intensity of discomfort.